An Overview of Childhood Ocular, Orbital and Surface Tumor with Clinical Updates - Roy, Soma Rani; Huque, Fahmida (Journal of National Institute of Ophthalmology, 2022)
Childhood tumor is different from but has a wide range varieties in types and presentation due to its origin from different embryogenic layers. Pediatric patients mostly depend on their parent or caregiver for seeking medical attention thus many ocular tumor present with unnecessary delay. Most childhood ocular tumors are benign but there are also life threatening tumors. In this paper a variety of intraocular, orbital and surface tumors are reviewed with their key sign of diagnosis and current treatment modalities. Though most of these tumor present at tertiary eye hospital, the overall knowledge about these tumors can help ophthalmologists in diagnosis and proper referral. J. Natl. Inst. Ophthalmol. 2022;5(1):51-68